Phaeospora rimosicola (Verrucariaceae, Ascomycota) – new species of lichenicolous fungi for Ukraine - M. V. Pirogov; S. M. Sharavara (Біологічні студії, 2012)
The data concerning species of lichenicolous fungi – Phaeospora rimosicola (Leight. ex Mudd) Hepp ex Stein that is new for Ukraine, are presented. Ph. rimosicola differs from morphologically similar species, Muellerella lichenicola (Sommerf.) D. Hawksw., having 3–4-septate spores and 8-spores asci and from related species, Phaeospora parasitica (Lönnr.) Arnold, having perithecia, asci and ascospores with smaller sizes.